Psycho-Social Correlates of Opioid Use Disorder among the US Adult Population: Evidence from the National Survey on Drug Use and Health, 2015–2018 - Haider, Mohammad Rifat (Subst Use Misuse, 2020)
BACKGROUND: The United States (US) has experienced an opioid epidemic over the last two decades. Drug overdose deaths increased by 21% from 2015 to 2016, with two-thirds of these deaths attributed to opioid use disorder (OUD). This study assessed the psycho-social correlates associated with OUD over 2015–2018 in the US. METHODS: This study used data collected from 171,766 (weighted = 245,838,163) eligible non-institutionalized US adults in the pooled National Survey on Drug Use and Health from 2015–2018. Survey-weighted descriptive, bivariate, and multivariable analyses were performed to assess the psycho-social correlates of OUD. RESULTS: About 0.85% of the respondents reported having OUD in the past year. About one-quarter (26.3%), one-sixth (14.8%), and half (47.3%) of the respondents with OUD reported alcohol, marijuana, and nicotine dependence, respectively. One-sixth (16.7%) had a criminal justice involvement history, and almost one-third (30.8%) experienced a major depressive episode (MDE) in the past year. In multivariable analysis, ≤64 years, White race, male gender, lower educational attainment, unemployment, large metro area residence, history of alcohol, marijuana, nicotine use disorder, history of criminal justice involvement, and MDE in previous year were associated with higher odds of OUD. In contrast, being married, non-Hispanic African American, non-Hispanic Other, and Hispanic ethnicity, good physical health, private health insurance, and higher risk perception about addictive substance use were associated with lower odds of OUD. CONCLUSIONS: OUD is more prevalent among certain sociodemographic groups in the US. Targeted interventions focusing on young, White, unmarried, male, and uninsured/Medicaid/Medicare populations should be implemented to reduce the OUD.